Analytical quality by design in the development of a solvent-modified micellar electrokinetic chromatography method for the determination of sitagliptin and its related compounds - Pasquini, Benedetta; Gotti, Roberto; Villar-Navarro, Mercedes; Douša, Michal; Renai, Lapo; Del Bubba, Massimo; Orlandini, Serena; Furlanetto, Sandra (Journal of pharmaceutical and biomedical analysis, 2021)
A solvent-modified micellar electrokinetic chromatography method was developed following the Quality by Design approach for the simultaneous determination of sitagliptin (SIT), an oral antihyperglycemic drug, and its main impurities derived from the synthesis process. The separation system was identified in the scouting phase and was made by sodium dodecyl sulphate (SDS) micelles with the addition of n-butanol and methanol. The knowledge space was investigated through an asymmetric screening matrix, taking into consideration eight critical method parameters (CMPs) involving the composition of the background electrolyte in terms of buffer concentration and pH, the concentration of surfactants and organic modifiers, and voltage. The critical method attributes (CMAs) were identified as analysis time and the distance between the tail of the electroosmotic flow system peak and the front edge of impurity I1 (sitagliptin triazole hydrochloride). A Box-Behnken Design was used in response surface methodology for calculating the quadratic models relating the CMPs to the CMAs. From the models it was possible to compute the method operable design region (MODR) through Monte-Carlo simulations. The MODR was identified in the probability maps as the multidimensional zone where the risk of failure to achieve the desired values for the CMAs was lower than 10 %. The experimental conditions corresponding to the working point, with the MODR interval, were the following: background electrolyte, 14 (10-18) mM borate buffer pH 9.20, 100 mM SDS, 13.6 (11.1-16.0) %v/v n-butanol, 6.7 (4.5-8.8) %v/v methanol; voltage and temperature were set to 28 kV and 22 °C, respectively. The developed CE method was validated in accordance with International Council for Harmonisation guidelines and was applied to the analysis of SIT tablets. The routine analysis for the quality control of the pharmaceutical product could be conducted in about 11 min.
Keywords: Micelles; micely; Capillary electrophoresis; Reproducibility of Results; Sitagliptin Phosphate; Chromatography, Micellar Electrokinetic Capillary; Method operable design region; Quality by design; Solvents; reprodukovatelnost výsledků; Experimental design; rozpouštědla; Sodium Dodecyl Sulfate; Impurities; chromatografie micelární elektrokinetická kapilární; Sitagliptin; sitagliptin fosfát; dodecylsíran sodný